Upaya Meningkatkan Regulasi Diri Siswa Sekolah Inklusi Melalui Metode Journaling - Zuraida, Dita Juwita; Fajri, Nurul; Hasna, Afra; Prawata, Yusuf Maulana; Fikrianto, Misbah (Universitas Negeri Makassar, 2025)
When students enter junior high school, many students have difficulty adapting to junior high school life, both in terms of academic, social, and independence. High self-regulation is needed for students to adapt well in junior high school. It is very important to train students to have high self-regulation, especially when students are just entering junior high school, namely in grade 7. Journaling method was chosen as one of the tools to improve students' self-regulation. This study only uses 2 (two) variables, namely: 1) Self-regulation, 2) Journaling Method; so that the research objectives are to obtain an overview of the use of journaling method to help improve students' self-regulation and obtain an overview of the effectiveness of using journaling method to help improve students' self-regulation. This research uses the Classroom Action Research method. The method was chosen because Classroom Action Research aims to solve real problems that occur in the classroom through actions taken in the classroom. This research was conducted at SMP Madania Parung, Bogor which is an inclusive school